Juristic methods of purifying haram incomes: An analysis in the context of Islamic banks in Malaysia abstract - Mohd Yunus, Saidatolakma; Haneef, Sayed Sikandar Shah; Kamaruddin, Zuraidah (International Islamic University Malaysia, 2017)
This study is an attempt to articulate juristic mechanisms by which Islamic banks in Malaysia can purge the unlawful incomes from their assets. Islamic bank being a modern corporate entity when dealing with people of diverse cultures and conventional business entities, at times feel the pressure of not being able to stay away from transactions tainted with haram. Islamic banks as a matter of principle should not involve themselves in any unlawful business activities in the process of which they can procure unlawful incomes. A question of how Islamic banks in Malaysia should treat such incomes, both classical and contemporary jurists have proposed their own set of juristic methods. This study provides recommendations to the Islamic banks in order to address the importance of undertaking the purification process of haram income according to Shariah.